Efficacy and safety of complement inhibitors in patients with geographic atrophy associated with age-related macular degeneration: a network meta-analysis of randomized controlled trials - Wang, Huan; Zheng, Jiaqi; Zhang, Qing; Tian, Zhongping; Sun, Yuhang; Zhu, Tianyi; Bi, Yanlong; Zhang, Li (Frontiers in Pharmacology, 2024)
Importance: Clinical trials in recent years have shown great promise for geographic atrophy (GA) treatment though complement inhibitors. Two complement inhibitor drugs have been approved by the Food and Drug Administration. Objective: To compare and rank the different complement inhibitors in the treatment of GA secondary to age-related macular degeneration (AMD). Data Sources: A systematic literature search was conducted in the Cochrane Central, Web of Science Core Collection, PubMed, LWW Medical Journals, ClinicalTrials.gov and WHO ICTRP from inception to October 2023. Study Selection: All randomized clinical trials evaluating the effectiveness of complement inhibitors in patients diagnosed with secondary GA in AMD were identified.